Learning to believe in Papua New Guinea - Andersen BA (Palgrave Macmillan, 2017)
This chapter examines how witchcraft and sorcery beliefs are reproduced among the educated working and middle classes in Papua New Guinea. In a context where tertiary schooling is accessible only to a tiny segment of the population, many educated people in PNG feel anxious about their social position and worry that their upward mobility will provoke envy and resentment in the less fortunate. This anxiety is projected most strongly onto the “ples lain” or rural population, who are thought to maintain many traditional practices, including witchcraft and sorcery. Drawing on ethnographic research among nursing students in the Eastern Highlands, I examine the ways that class identity and Pentecostal social forms coalesce, giving students resources for narrating, understanding, and resisting the dangers they face as social outsiders and (future) employees of a neglectful state. Looking specifically at events during a nursing practicum in rural Eastern Highlands Province, I describe how students and their teachers collapsed different forms of invisible violence—both traditional and contemporary—into a generic evil to be discerned and resisted. Following Robbins (2009) I argue that witchcraft talk is exceptionally socially productive—in this case, productive of a distinctly Christian, professional class identity in which the problems created by “the villagers” and “pasin tumbuna” (ancestral practices) are objects of profound concern.